Introducing Zurb Foundation 6 - Shenoy, Aravind (Apress : Imprint: Apress, 2016)
Introducing Zurb Foundation 6 is your easy-to-digest brief introduction to this exciting technology for building responsive and mobile-first websites. Using this book, you'll understand the basics of the latest iteration which comes with new and exciting features. You will understand how to incorporate Foundation into your HTML file and the various options you have, including typography, utility classes, media, forms, buttons and much more. This book will jumpstart your knowledge with an easy-to-follow approach so you can come to grips with the latest version of the framework. A downloadable code bundle is also included for you to play with, and therefore understand, the subtle nuances of the latest version. What You Will Learn •How to download and incorporate Zurb Foundation into your workflow •How to use the new grid system, layout, content, and further features •How to design interfaces and other web elements using built-in CSS and JavaScript components Who This Book Is For This book is aimed at beginners who have a basic understanding of HTML, CSS and JavaScript and want a quick, no-nonsense introduction to working with Zurb Foundation. No prior experience or knowledge of Zurb Foundation 5 or its previous versions is required to understand the concepts in this book.